2015
DOI: 10.1007/s11367-015-0877-8
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of bioethanol production pathways in China based on life cycle sustainability assessment and multicriteria decision-making

Abstract: Purpose The study objectives are twofold: (i) combining the life cycle sustainability assessment (LCSA) framework and the multicriteria decision-making (MCDM) methodology for sustainability assessment and (ii) determining the most sustainable scenario for bioethanol production in China according to the preferences of the decision-makers/stakeholders. Methods Life cycle assessment (LCA), life cycle costing (LCC), and social life cycle assessment (SLCA) are combined to collect the corresponding criteria data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(89 citation statements)
references
References 60 publications
0
79
0
1
Order By: Relevance
“…Results of this study indicated that noise pollution and air quality were the important criteria of environmental quality in Taipei. Vučijak, Kupusović, Midžić-Kurtagić andĆerić [3] evaluated sustainable hydropower by applying the VIKOR, Quijano H, Botero B and Domínguez B [4] used VIKOR for development of renewable sustainable energy plans, Martin-Utrillas, Juan-Garcia, Canto-Perello and Curiel-Esparza [6] integrated the VIKOR, fuzzy Delphi and AHP for selection of best infrastructure related to sustainable economy, Ren, Manzardo, Mazzi, Zuliani and Scipioni [8] combined the VIKOR and AHP for assessment of life cycle sustainability, Yazdani-Chamzini, Fouladgar, Zavadskas and Moini [7] used the VIKOR, SAW, ARAS, TOPSIS and MOORA for selection of the best renewable energy sources, Civic and Vucijak [9] utilized VIKOR for insulation options for warmth of buildings to increase energy efficiency, Kim and Chung [10] evaluated the vulnerability of the water supply to variability and climate change. In total, 13 past papers used the VIKOR technique in the fields of sustainability and renewable energy, which presented in Table 10.…”
Section: Sustainability and Renewable Energy Fieldsmentioning
confidence: 99%
“…Results of this study indicated that noise pollution and air quality were the important criteria of environmental quality in Taipei. Vučijak, Kupusović, Midžić-Kurtagić andĆerić [3] evaluated sustainable hydropower by applying the VIKOR, Quijano H, Botero B and Domínguez B [4] used VIKOR for development of renewable sustainable energy plans, Martin-Utrillas, Juan-Garcia, Canto-Perello and Curiel-Esparza [6] integrated the VIKOR, fuzzy Delphi and AHP for selection of best infrastructure related to sustainable economy, Ren, Manzardo, Mazzi, Zuliani and Scipioni [8] combined the VIKOR and AHP for assessment of life cycle sustainability, Yazdani-Chamzini, Fouladgar, Zavadskas and Moini [7] used the VIKOR, SAW, ARAS, TOPSIS and MOORA for selection of the best renewable energy sources, Civic and Vucijak [9] utilized VIKOR for insulation options for warmth of buildings to increase energy efficiency, Kim and Chung [10] evaluated the vulnerability of the water supply to variability and climate change. In total, 13 past papers used the VIKOR technique in the fields of sustainability and renewable energy, which presented in Table 10.…”
Section: Sustainability and Renewable Energy Fieldsmentioning
confidence: 99%
“…Several authors chose to integrate multi-criteria decision analysis (MCDA) in order to be able to combine different indicators into one aggregated result, deriving weights for the respective indicators, and even translate qualitative information into quantitative metrics [48][49][50][51][52]. In order to determine weights, researchers usually applied fuzzy evaluation methods, the Analytical Hierarchy Process (AHP) or a combination of those to translate qualitative evaluations of experts into metrics [48][49][50][51]53].…”
Section: Multi-criteria Decision Analysismentioning
confidence: 99%
“…LC approaches assessing social-economic impacts such as SLCA, LCC, and LCSA are relatively novel methods, and call for further methodological development and practices of case studies. However, bioenergy is among one of the most assessed topics in existing studies [454][455][456]. Although the depth and breadth of LC approaches have developed rapidly in the past decades, further research is needed to consolidate important controversies and close methodological gaps.…”
Section: Sustainability Of Bioenergy Systemsmentioning
confidence: 99%